Electromagnetic Diffraction Modeling: High Frequency Asymptotics vs. Numerical Techniques - Levent Sevgi (Applied Computational Electromagnetics Society Journal (ACES), 2021)
Electromagnetic diffraction modelling and recent numerical simulation approaches, on the canonical 2D non-penetrable wedge scattering problem, are reviewed in this introduction paper.